1985
DOI: 10.1099/00222615-19-1-61
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the traT Gene to Serum Resistance Among Clinical Isolates of Enterobacteriaceae

Abstract: SUMMARY. Antimicrobial resistance plasmids containing the traT gene confer resistance to serum bactericidal activity upon some laboratory strains of Escherichia coli. We have examined the DNA of Enterobacteriaceae from human extraintestinal infections to determine the frequency of traT-like genes. DNA sequences homologous with traT were found among 58% of Escherichieae but among none of the Klebsielleae or Proteeae tested and were found as frequently among serum-sensitive E. coli as among serum-resistant strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…The cloned traT gene increases the serum resistance of unencapsulated strains when present in low copy number, whereas with encapsulated strains, higher copy numbers of traT must be present to affect serum resistance (8). traT is always carried on large IncF plasmids (259,359). Although traT is more common among extraintestinal isolates (58%) than fecal strains (38%) (259), it is not clearly associated in the aggregate with serum resistance (259,359), except possibly among UTI isolates (359), a finding which casts doubt on the importance of traT as a significant determinant of serum resistance in pathogenic strains.…”
Section: Plasmid-associated Proteins In Serum Resistancementioning
confidence: 91%
See 2 more Smart Citations
“…The cloned traT gene increases the serum resistance of unencapsulated strains when present in low copy number, whereas with encapsulated strains, higher copy numbers of traT must be present to affect serum resistance (8). traT is always carried on large IncF plasmids (259,359). Although traT is more common among extraintestinal isolates (58%) than fecal strains (38%) (259), it is not clearly associated in the aggregate with serum resistance (259,359), except possibly among UTI isolates (359), a finding which casts doubt on the importance of traT as a significant determinant of serum resistance in pathogenic strains.…”
Section: Plasmid-associated Proteins In Serum Resistancementioning
confidence: 91%
“…Several phenotypic traits other than colicin production per se may contribute to the virulence associated with ColV plasmids, including autoagglutination and hypomotility at 37°C (which may impede phagocytosis) (464,542,543), enhanced survival in the mouse peritoneum (419), increased adherence to mouse intestinal cells and increased fimbriation (65), aerobactin production (see above), impaired phagocytosis (9), and increased serum resistance (9,29,30,259,373,498,540,541). pColV, I-K94 (a well-studied ColV plasmid) also confers increased acid susceptibility (72).…”
Section: Plasmid-associated Proteins In Serum Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid conjugation is encoded in the tra region. It has been demonstrated that expression of traT genes might be involved in bacterial resistance to serum (181,270), biofilm development (141), and phagocytosis (3), therefore contributing to the virulent properties of bacteria carrying conjugative (frequently antibiotic resistance) plasmids.…”
Section: Evolution and Dissemination Of Genes Involved In Virulence Amentioning
confidence: 99%
“…Methods used for assay of hemolysin expression, serum resistance, and D-mannose-resistant hemagglutination (MRHA) of human erythrocytes have been described previously and were used without modification (9,12). Strains were identified as prototrophic or auxotrophic by testing for capacity to grow on minimal salts agar supplemented with 0.4% glucose (4).…”
Section: Methodsmentioning
confidence: 99%